2008
DOI: 10.1038/ncprheum0681
|View full text |Cite
|
Sign up to set email alerts
|

Primer: inflammasomes and interleukin 1β in inflammatory disorders

Abstract: Inflammasomes are large, multimeric protein complexes that link the sensing of microbial products and metabolic stress to the proteolytic processing of prointerleukin (pro-IL)-1beta to its active form. NALP1 and NALP2 are founding members of the Nod-like receptor family. Other Nod-like receptors, including NALP3 and NOD2, which are associated with inflammatory disorders, have also been described. The NALP1 and NALP3 inflammasomes are located in the cytoplasm and can, therefore, detect intracellular infection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
198
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(208 citation statements)
references
References 70 publications
4
198
0
4
Order By: Relevance
“…Reflecting the differential responsiveness at the transcriptome level, protein levels for the evaluated cytokines varied among these myeloid populations, as shown for IL-l␤, IL-6, and also TNF-␣ (Figure 3 and Figure 7, A and B). However, in keeping with the requirement for posttranscriptional inflammasome-mediated processing of the IL-l␤ precursor protein, 29 macrophages and DCs secreted little active IL-l␤ protein ( Figure 7A), despite Ն100-fold increases in gene expression ( Figure 7A and Supplemental Table S2 available at http://ajp.amjpathol. org).…”
Section: Cytokines and Co-stimulatory Molecules Associated With Innatsupporting
confidence: 54%
“…Reflecting the differential responsiveness at the transcriptome level, protein levels for the evaluated cytokines varied among these myeloid populations, as shown for IL-l␤, IL-6, and also TNF-␣ (Figure 3 and Figure 7, A and B). However, in keeping with the requirement for posttranscriptional inflammasome-mediated processing of the IL-l␤ precursor protein, 29 macrophages and DCs secreted little active IL-l␤ protein ( Figure 7A), despite Ն100-fold increases in gene expression ( Figure 7A and Supplemental Table S2 available at http://ajp.amjpathol. org).…”
Section: Cytokines and Co-stimulatory Molecules Associated With Innatsupporting
confidence: 54%
“…A variety of single point mutations within the nucleotide binding domain or leucine-rich repeats alter the function of NLRP3 (56). Yet very little is known about the molecular requirements for NLRP3 inflammasome activation; thus, it is plausible that differences confer a Francisella-responsive state to NLRP3 that Nlrp3 lacks.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 1 beta regulates inflammation signal pathway 28 and accelerates the expression level of MMP and TIMP. 29 It was reported that N-myc downstream regulated 1 regulates angiogenesis in hepatocellular carcinoma, 30 and B-cell leukemia/lymphoma 2 protein promotes apoptosis.…”
Section: Controlling Liver Fibrosis Through Preventionmentioning
confidence: 99%